(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article dedicates teaching English strategies, terminology and classification of strategies, the effects of learner characteristics on strategy use, the effects of culture and context on strategy use, explicit and integrated strategy instruction, language of instruction, transfer of strategies to new tasks, and techniques.